2022
DOI: 10.3390/bioengineering9120729
|View full text |Cite
|
Sign up to set email alerts
|

New Insight into Muscle-Type Cofilin (CFL2) as an Essential Mediator in Promoting Myogenic Differentiation in Cattle

Abstract: Meat quality and meat composition are not separated from the influences of animal genetic improvement systems; the growth and development of skeletal muscle are the primary factors in agricultural meat production and meat quality. Though the muscle-type cofilin (CFL2) gene has a crucial influence on skeletal muscle fibers and other related functions, the epigenetic modification mechanism of the CFL2 gene regulating meat quality remains elusive. After exploring the spatiotemporal expression data of CFL2 gene in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Recent research has shown that the marker genes MYOD , MYOG , and MYH3 controlled the differentiation of primary myoblasts [ 52 ]. As additional research comes to light, it is becoming increasingly clear that MYOD played a crucial role in myogenic differentiation, which promotes myogenin expression and eases myocyte fusion [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that the marker genes MYOD , MYOG , and MYH3 controlled the differentiation of primary myoblasts [ 52 ]. As additional research comes to light, it is becoming increasingly clear that MYOD played a crucial role in myogenic differentiation, which promotes myogenin expression and eases myocyte fusion [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, Liu et al [ 47 ] found that Zbed6 +/− may promote muscle growth in mice by upregulating Barx2 . Additionally, CFL2 , serving as a crucial mediator in promoting bovine myogenic differentiation, facilitates the differentiation of bovine myoblasts through the regulation of muscle differentiation marker gene expression [ 48 ]. The signal visualization revealed a consistent trend in the signals of ATAC-seq and RNA-seq for FOXO1 and CRY2 , both exhibiting robust signals in Jeryak.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the Six1 gene, a potent regulator of skeletal muscle development [45], activates myogenesis and enhances Myf3 expression by specifically binding to the MEF5 site in the promoter of the gene, thereby promoting skeletal muscle development [46,47]. Sun et al [48]. reported a significant upregulation of CFL2 expression in skeletal muscle, which plays a crucial in regulating the activity of transcription factors involved in muscle formation within C2C12 cells and this, in turn, has an impact on the proliferation and differentiation of myofibroblasts.…”
Section: Discussionmentioning
confidence: 99%